2021
DOI: 10.1038/s41467-021-22751-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain-specific lipoprotein receptors interact with astrocyte derived apolipoprotein and mediate neuron-glia lipid shuttling

Abstract: Lipid shuttling between neurons and glia contributes to the development, function, and stress responses of the nervous system. To understand how a neuron acquires its lipid supply from specific lipoproteins and their receptors, we perform combined genetic, transcriptome, and biochemical analyses in the developing Drosophila larval brain. Here we report, the astrocyte-derived secreted lipocalin Glial Lazarillo (GLaz), a homolog of human Apolipoprotein D (APOD), and its neuronal receptor, the brain-specific shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 84 publications
5
28
0
Order By: Relevance
“…In this respect, the hypothesis of ApoD working on oxidized lipid "whiskers" (Greenberg et al, 2008;Del Caño-Espinel, 2014) on cell membrane bilayers or lipoparticles is appealing and worth contrasting. 6) Recent studies on a Drosophila homolog (Yin et al, 2021) point to lipid droplets as another higher-order lipid structure susceptible to be modulated by ApoD. Searching for lipid droplet-managing functions of vertebrate ApoD is therefore pertinent.…”
Section: Future Goals For Apod Biologymentioning
confidence: 99%
“…In this respect, the hypothesis of ApoD working on oxidized lipid "whiskers" (Greenberg et al, 2008;Del Caño-Espinel, 2014) on cell membrane bilayers or lipoparticles is appealing and worth contrasting. 6) Recent studies on a Drosophila homolog (Yin et al, 2021) point to lipid droplets as another higher-order lipid structure susceptible to be modulated by ApoD. Searching for lipid droplet-managing functions of vertebrate ApoD is therefore pertinent.…”
Section: Future Goals For Apod Biologymentioning
confidence: 99%
“…Moreover, optogenetic/chemogenetic and calcium imaging techniques have been combined with trans-Tango to understand the functional connectivity between preand postsynaptic neurons (Guo et al, 2018;He et al, 2019;Feng et al, 2020). TRACT has been used to label postsynaptic neurons in olfactory and rhythm circuits (Huang et al, 2017), as well as glial cells (Yin et al, 2021). BAcTrace has been applied to show synaptic connections from olfactory projection neurons to olfactory receptor neurons and Kenyon cells of mushroom bodies and lateral horn neurons (Cachero et al, 2020).…”
Section: Applications Of Genetic Transsynaptic Toolsmentioning
confidence: 99%
“…The copyright holder for this this version posted November 11, 2021. ; https://doi.org/10.1101/2021.11.10.467940 doi: bioRxiv preprint morphogenesis and function, and future studies should address its interaction with other pathways involved in these processes. [11] shows that a short isoform of LpR1 (LpR1G) interacts with the lipocalin Glaz. Interestingly, a report from the Bellen group shows that the transport of lipids between neurons and glia is mediated by Glaz and neural lazarillo proteins (Nlaz), the orthologs for ApoD in flies [82].…”
Section: Lprs Are Required For Adult Mb Structure and Operationmentioning
confidence: 99%
“…Moreover, in the case of LpR1, this effect depends on the short isoforms. Specifically, it was reported that knocking down a specific LpR1 short isoform (LpR1G) or LpR2 in LNv reduces activity-dependent dendrite arborization [11,12]. Since a genome-wide RNAi screen in cultured neurons from D. melanogaster embryos identified LpR2 as a gene implicated in neuronal development [13] and given the fact that LpR1 and LpR2 are widely expressed in the Drosophila larval brain [11,12], it is possible to propose that LpRs could contribute to the development, maturation and operation of several fly brain regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation